PENGARUH PERILAKU TEMAN SEBAYA TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SMP NEGERI 01 RANAH BATAHAN KABUPATEN PASAMAN BARAT - Susana, Novia; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
Problems study researchers phenomenon is found in the field of peer behavior on studentâs motivation at this time in school environment is less in line with what it should be. Study the researches raised concerns about how the behavior of peers to influence student motivation in the realm of SMPN 01 Ranah Batahan, West Pasaman. This study aimed to determine the influence of peers on studentâs motivation in SMPN 01 Ranah Batahan, West Pasaman aimed to describe the behavior of peers learners, studentâs motivation, influence of peer behavior with studentâs motivation. Research type the used descriptive correlation. The population in this study were students of SMPN 01 Ranah Batahan, West Pasaman. The sample in this study using stratified random sampling technique. From the calculations, as sample of go people the instrument used in this study was a questionnaire. To analyze the data used Pearson Product Moment Formula (PPM) in order to see the relationship between the influence of peer behavior and motivations of learners in SMPN 01 Ranah Batahan, West Pasaman.Results of this research indicate that there are behavior of peer reside in at high enough and to motivation learn to reside in at high frequency.